More answers

Assuming it is x to power 4 multiplied by x to power 2 then the result is multiplied by 3xto power 2; then the result is 3 x to power 4+2+2 that equal 3 multiplied by x to power 8

Q: What is (x 4)(x2 3x 2)?

Write your answer...

Submit

Still have questions?

Continue Learning about Other Math

(x3 + 4x2 - 3x - 12)/(x2 - 3) = x + 4(multiply x2 - 3 by x, and subtract the product from the dividend)1. x(x2 - 3) = x3 - 3x = x3 + 0x2 - 3x2. (x3 + 4x2 - 3x - 12) - (x3 + 0x2 - 3x) = x3 + 4x2 - 3x - 12 - x3 + 3x = 4x2 - 12(multiply x2 - 3 by 4, and subtract the product from 4x2 - 12)1. 4x(x - 3) = 4x2 - 12 = 4x2 - 122. (4x2 - 12) - (4x2 - 12) = 4x2 - 12 - 4x2 + 12 = 0(remainder)

The operators are missing, the possible factorisations are:4x2 + 10x + 6 = 2(2x + 3)(x + 1)4x2 - 10x + 6 = 2(2x - 3)(x - 1)4x2 + 10x - 6 = 2(2x - 1)(x + 3)4x2 - 10x - 6 = 2(2x + 1)(x - 3)

3x * (x - 4) = 3x*x - 3x*4 = 3x^2 - 12x.

If you mean: x2+3x+2 then it is (x+1)(x+2) when factored

3x^2

Related questions

(x3 + 4x2 - 3x - 12)/(x2 - 3) = x + 4(multiply x2 - 3 by x, and subtract the product from the dividend)1. x(x2 - 3) = x3 - 3x = x3 + 0x2 - 3x2. (x3 + 4x2 - 3x - 12) - (x3 + 0x2 - 3x) = x3 + 4x2 - 3x - 12 - x3 + 3x = 4x2 - 12(multiply x2 - 3 by 4, and subtract the product from 4x2 - 12)1. 4x(x - 3) = 4x2 - 12 = 4x2 - 122. (4x2 - 12) - (4x2 - 12) = 4x2 - 12 - 4x2 + 12 = 0(remainder)

If the missing signs are all pluses, that's 4x2 + 3x + 3

3(4x2 - x + 2)

4x2 - 2x - 12= 2x2 - x - 6= 2x2 - 4x + 3x - 6= 2x(x - 2) + 3(x - 2)= (x - 2)(2x + 3)

2x+x is 3x

4x2 + 3x - 6 is a second degree polynomial. Since the polynomial function f(x) = 4x2 + 3x - 6 has 2 zeros, it has 2 linear factors. Since we cannot factor the given polynomial, let's find the two roots of the equation 4x2 + 3x - 6 = 0, which are the zeros of the function. 4x2 + 3x - 6 = 0 x2 + (3/4)x = 6/4 x2 + (3/4)x + (3/8)2 = 6/4 + 9/64 (x + 3/8)2 = 105/64 x + 3/8 = ± √(105/64) x = (-3 ± √105)/8 x = -(3 - √105)/8 or x = -(3 + √105)/8 Thus, the linear factorization of f(x) = 4[x + (3 - √105)/8][x + (3 + √105)/8].

3x-3x+4x^2+8x=4x^2+8x

sorry it wouldn't let me put brackets in. it should read 3x^2 -2x + (2-x)^2 = 2 3x2-2x+4-4x+x2=2 4x2-6x+4=2 4x2-6x+2=0 2(2x2-3x+1)=0 2(x-1)(2x-1)=0 x=1 or x=1/2

-4x2 + 5x + 6 = 0 Multiply through by -1: 4x2 - 5x - 6 = 0 (I prefer the leading coefficient to be >0) 4x2 - 8x + 3x - 6 = 0 4x(x - 2) + 3(x - 2) = 0 (x - 2)(4x + 3) = 0 So x - 2 = 0 or 4x + 3 = 0 ie x = 2 or x = -3/4

y=4x2+3x+8

2 x 2 x 3 x 2 x 2 x 7 x 2 x 2 x 2 = 27 x 3 x 7 or 2688

The first equality is: x2 - 5 = -4x2 which gives 5x2 - 5 = 0 which is equivalent to x2 - 5 = 0 The second equality is: -4x2 = 3x which gives 4x2 + 3x = 0 The two results are inconsistent.